2000
DOI: 10.1002/jor.1100180220
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance of standard and cannulated 4.0‐mm cancellous bone screws

Abstract: The mechanical performance of bone screws is determined by their pull-out strength (holding power), compressive force, stripping torque, yield bending moment, ultimate bending moment, and fatigue strength. These parameters are related to the parameters of the screw design, including major thread diameter, minor thread diameter, thread length, pitch, shaft diameter, cannulation diameter, and material properties. The goal of the study was to theoretically predict the static performance of five 4.0-mm, 45-46-mm-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Brown et al suggested that predicted values for pullapart force were determined by the thread length, major thread diameter, and thread shape. 10 The Kompressor screw has a trailing thread diameter of 5.0 mmgreater than the trailing thread diameter of other screws Little Grafter 27…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Brown et al suggested that predicted values for pullapart force were determined by the thread length, major thread diameter, and thread shape. 10 The Kompressor screw has a trailing thread diameter of 5.0 mmgreater than the trailing thread diameter of other screws Little Grafter 27…”
Section: Discussionmentioning
confidence: 97%
“…Wheeler et al used a push-out test to quantify the specific resistance of a screw to axial loading and found that the Acutrak screw showed significantly greater push-out force than the AO or Herbert screw. 6 Other studies 3,9,10 have investigated the pullout strength. Brown et al suggested that predicted values for pullapart force were determined by the thread length, major thread diameter, and thread shape.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was the same as the results of the past studies mentioned above. Brown et al [20] concluded that simple-beam theory is capable of providing enough evidence to support the optimization of the design of cylindrical bone screws. In the present study, the area moment of inertia for each spinal pedicle screw was calculated to validate this finding.…”
Section: Discussionmentioning
confidence: 99%
“…In intramedullary nail [25] the introduction of a slot in a lag screw increases deformation and reduces stress, while the displacements in a trochanteric fracture were similar between a Gamma nail and a PFN [26]. The same finite element model of a femur with a Gamma nail implant produced greater deformation of a subtrochanteric fracture than a femoral neck fracture [27] and the deformation was reduced with the inclusion of an iliospoas force. These studies highlight the strength of finite element analysis in producing a wide range of findings that can be transferred to the clinical application of fixation techniques.…”
Section: Introductionmentioning
confidence: 95%
“…In healthy patients with a long life expectancy and with the likelihood for the return to everyday activities, the most app1ropriate treatment for fractures of the femoral neck is minimally invasive surgery to reduce the fracture and provide adequate stabilisation [5]. For undisplaced intracapsular fractures of the femoral head and neck, the use of cannulated hip screws to achieve adequate fixation is advocated [3][4][5][6][7][8][9]. Achieving immobilization of the fractured surfaces to allow adequate callus formation during the immediate post-operative period is an important factor for satisfactory bone healing [10].…”
Section: Introductionmentioning
confidence: 99%